Analysis of Government Policies Regarding Zoning System for Acceptance of New Students - Mufidah, Anisah; Ramadhana, Fisca Amanda; Lidya Siboro, Ruth; Ivanna, Julia (Berpusi Publishing, 2023)
The Indonesian government is carrying out various strategies in an effort to improve quality in the field of education, namely by issuing a Minister of education and culture regulation contained in Number 14 of 2018 concerning Acceptance of New Students. The implementation of the zoning-based PPDB policy is one of the right policies for equal distribution of access and quality of education because the principle is to bring education services closer to the community and equalize the quality of education. However, in reality, the implementation of this zoning system resulted in an even distribution of education from only one perspective, namely making it easier to guide and teach students, but racing in the field of diversity was minimal. This research uses a descriptive research type, with library research data collection techniques.